Workload and Work Discipline on Teacher Performance at SMA Diponegoro Tumpang: Literature Review Study - Fitria, Ana Sichatul; Kristin, Muria; Nandang WP; Rokhman, M. Taufiq Noor (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to look at how work discipline and workload affect teachers' effectiveness at SMA Diponegoro Tumpang. Teacher performance in schools is a crucial aspect in achieving quality education goals. However, factors influencing their performance, such as workload and level of work discipline, are not fully understood in the context of senior high schools. This study employs a literature review method to examine the contribution of workload and work discipline to teacher performance. Through a review of related studies, this research aims to identify the relationship between the workload faced by teachers and their level of work discipline with their performance in the context of SMA Diponegoro Tumpang. The expected outcomes of this research are a deeper understanding of how workload and work discipline affect teacher performance at SMA Diponegoro Tumpang. The implications of these findings are expected to provide valuable insights for school management in designing policies that support the improvement of teacher performance, and serve as a foundation for further research in this area.